Study on Durability of Waterproofing Membrane Polyvinyl Chloride for Flat Roof - Hasli , Nur Saffa Zuhrah; Saji, Nurdalila (Progress in Engineering Application and Technology, 2021)
A house is a human dwelling that has walls and a roof that can withstand wind, heat, cold, and rain. The choice of roof for a building plays a role in terms of tidiness and comfort. In Malaysia, the selection of flat roofs is often used because it makes a residence look modern and majestic. Therefore, the problems that occur if the quality of leaks, weaknesses in the connection, and reduction of the use of waterproofing materials on the roof. So, the risk that will occur if the cause is not emphasized is that the moldy roof, ceiling, and water will absorb the building elements. The objective of this study is to examine the level of knowledge on the use of Polyvinyl Chloride (PVC) membrane on the roof of the building and to examine the level of thermal comfort of buildings using flat roofs in Malaysia. The scope of the study is divided into two, namely the questionnaire on the level of knowledge about the waterproof layer on the roof of the building and make a virtual study on the level of thermal comfort of the building for homes that use flat roofs. The data obtained from this study are respondents from students of the Faculty of Engineering Technology about the level of knowledge about the waterproof layer of PVC membrane is very encouraging and it is a very effective technique in keeping the house dry and preventing leakage. Finally, every housing should apply this technique in roof construction on these factors because Malaysia is close to the equator where weather and climate changes are sometimes rainy and hot.